2020
DOI: 10.1166/sam.2020.3643
|View full text |Cite
|
Sign up to set email alerts
|

Novel Poly(vinyl alcohol)/Clay Nanocomposite Film Prepared by the Heterogeneous Saponification of Poly(vinyl acetate)/Clay Nanocomposite Film

Abstract: A novel PVA/clay (MMT) film is prepared for the first time based on the saponification of the PVAc/MMT film in the presence of heterogeneous conditions. With the help of optical microscopy, the characteristics and surface morphology of the saponified PVA/MMT film is confirmed. It is found to contain black MMT nanoparticles in PVAc films as the content of MMT increased. According to atomic force microscopy results, PVAc/MMT films shows unexpected surface roughness owing to the slow progress of the saponificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Meanwhile, the saponified PVAc film showed a -OH stretch in the range of 3000-3600 cm −1 that originated from both intermolecular and intramolecular hydrogen bonds, which meant the acetyl group (-OCOCH 3 ) of PVAc film turned to a hydroxyl group (-OH) due to the reaction with alkaline solution during heterogeneous saponification, which revealed that PVA was obtained from PVAc. A similar result was also found in our previous studies [20,27]. Figure 4b,c also show a similar trend regarding the saponified films, but the peak intensity varied depending on the PVAc/PULL ratio, which might be due to the change in material property.…”
Section: Ft-ir Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…Meanwhile, the saponified PVAc film showed a -OH stretch in the range of 3000-3600 cm −1 that originated from both intermolecular and intramolecular hydrogen bonds, which meant the acetyl group (-OCOCH 3 ) of PVAc film turned to a hydroxyl group (-OH) due to the reaction with alkaline solution during heterogeneous saponification, which revealed that PVA was obtained from PVAc. A similar result was also found in our previous studies [20,27]. Figure 4b,c also show a similar trend regarding the saponified films, but the peak intensity varied depending on the PVAc/PULL ratio, which might be due to the change in material property.…”
Section: Ft-ir Spectroscopysupporting
confidence: 90%
“…A similar result was also found in our previous studies [20,27]. Figure 4b,c also show similar trend regarding the saponified films, but the peak intensity varied depending o the PVAc/PULL ratio, which might be due to the change in material property.…”
Section: Xrdsupporting
confidence: 89%
See 1 more Smart Citation